Non-melodic intonational morphemes in English and Croatian - Josipović, Višnja (Array, 1997)
This paper provides a comparison of the inventories of non-melodic intonational morphemes (phrase and boundary tones) of English and Croatian within the framework of the bitonal generative compositional model. It is shown that the two languages have the same bitonal inventory of non-melodic tones, but English uses H tones from this category more frequently than Croatian does. It is suggested that Croatian makes up for these H tones by resorting more often to some alternative means of expression.